Assessment of a coupled approach to determine the stress caused by gun blast loads. (October 2021) - Costa, Emiliano
This paper aims at assessing a custom numerical procedure built to predict the level of stress in the structural components and equipment in proximity of a cannon-like weapon system when firing. In such a blast scenario, the structures adjacent to a gun may undergo sudden and unwanted damages, since they are commonly subjected to the blast load due to the impingement and propagation of the shock waves expanding from the weapon muzzle. The proposed procedure pertains the coupled use of an in-house developed tool (GUNWave3D) based on the power-law scaling technique and a general-purpose commercial fast dynamic solver to compute the structural response of the loaded components. The in-house tool, in particular, allows one to rapidly calculate the blast parameters over the surfaces of the items of interest in the function of the weapon characteristics and launch conditions, also accounting for the asymmetric shape characterizing the gun blast wave. Taking as reference the numerical free field peak overpressure profiles of a 30 mm gun, whose blast quantities were already validated in a previously published work, the final stage of the assessment was accomplished. Such an estimation consists of the comparison between the structural stresses calculated using the blast loads predicted through the in-house tool and those computed adopting the free spherical air blast of the tri-nitro-toluene model. This operation has the objective to quantify the discrepancy between the computational results of two Lagrangian techniques that can be alternatively adopted in industrial gun blast design procedures and methodologies.